Penerapan terapi spiritual emotional freedom technique (SEFT) pada penderita tuberculosis dengan masalah keperawatan di Puskesmas Sawahan - Eppy Setiyowati; Alfin Hidayatur Rahman (Universitas Nahdlatul Ulama Surabaya, 2020)
Abstract: Pulmonary tuberculosis (TB) is an infectious disease caused by rod-shaped bacteria (bacilli) known as Mycobacterium tuberculosis. This tubercle basil will cause respiratory problems. In addition, the disease process and long-term treatment often cause anxiety in people with Tuberculosis. The purpose of this study was the application of SEFT therapy in Tuberculosis patients to reduce anxiety in Sawahan Surabaya Health Center. The method used was descriptive with a case study approach through nursing care with anxiety nursing problems in Tuberculosis patients. Data collection is done using the method of interviews, direct observation, and medical records. The results of the application of SEFT therapy were carried out once / day for 3 days at Mr. B. There was a decrease in anxiety which was resolved gradually after SEFT therapy. The application of SEFT therapy is effective in reducing anxiety felt by Tuberculosis patients. Therefore nurses are expected to be able to teach SEFT therapy according to standard operating procedures (SOP) so that patients and families can practice it again at home.